Vocal Folds' Oscillatory Characteristics After Photoangiolytic Laser Treatment Using the Blue Light Laser-A Pilot Study - Echternach, Matthias; Döllinger, Michael; Richter, Bernhard; Köberlein, Marie (Journal of Otolaryngology-Head & Neck Surgery, 2026)
ImportancePhonosurgical treatments with photoangiolytic lasers, including blue light lasers, are increasingly common, yet effects on vocal fold oscillation patterns post-surgery are not fully understood.ObjectiveThe primary objective was to investigate changing oscillation patterns and recovery time of vocal fold oscillation after blue light laser phonosurgery in patients with unilateral vocal fold pathology.DesignProspective observational study following the STROBE guidelines, reporting pre- and post-intervention outcomes.SettingThe study was conducted in a clinical phonosurgical department specializing in vocal fold pathology.ParticipantsEight patients with unilateral vocal fold pathology were included. Eligibility was determined based on the necessity for phonosurgery.Intervention or ExposuresEach patient underwent phonosurgical treatment using a blue light laser. Vocal fold function was assessed preoperatively, 2 hours after surgery, 24 hours post-surgery, and 3 weeks following surgery. For the assessment, the subjects phonated on the vowel /i/ at a comfortable pitch and loudness.Main Outcome MeasuresHigh-speed videolaryngoscopy, electroglottography, and audio recordings were used to assess changes in vocal fold oscillations. Main metrics included amplitude symmetry index, jitter, cepstral peak prominence, and Open Quotients.ResultsTwo hours after surgery, an impairment in vocal fold oscillations on the treated side was observed, with a decrease in amplitude symmetry and an increase in electroglottographic jitter. Cepstral peak prominence was reduced, suggesting early effects on vocal fold vibration quality. By 24 hours and 3 weeks post-surgery, most parameters returned to preoperative values. However, the Open Quotient remained lower than pre-surgery levels at the 3-week follow-up, indicating a lasting change in glottal function.ConclusionsVocal fold oscillation recovers relatively quickly after blue light laser treatment, generally returning to baseline within 24 hours.RelevanceThis study highlights the temporary nature of vocal fold impairments following blue light laser surgery, providing insights for patient recovery expectations and voice rest recommendations.Clinical TrialGerman Clinical Trials Register, number DRKS00035411 https://www.drks.de/DRKS00035411.
CRIS-Team Scopus Importer:2026-02-06
Keywords: blue light laser; laryngology; phonosurgery; vocal fold mass lesions; vocal fold oscillations